2019
DOI: 10.1039/c9ob00541b
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c–poly(acrylic acid) conjugates with improved peroxidase turnover number

Abstract: Cytochrome c–poly(acrylic acid) conjugates with 34-fold enhanced peroxidase activity due to acidification of enzyme microenvironment and suppression of wasteful intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…When substrate concentration is excessive, k cat tends to V max . 26 Therefore, the k cat of free and immobilized enzymes was 0.060 and 0.040 s –1 , respectively, the k cat / K m of the free and immobilized pectinase was 0.005 and 0.003 mg –1 ·s –1 ·mL, respectively. V max , k cat , and k cat / K m decreased possibly because the substrate could not bind to the active sites of the immobilized pectinase because of the increased diffusion limitation.…”
Section: Resultsmentioning
confidence: 91%
“…When substrate concentration is excessive, k cat tends to V max . 26 Therefore, the k cat of free and immobilized enzymes was 0.060 and 0.040 s –1 , respectively, the k cat / K m of the free and immobilized pectinase was 0.005 and 0.003 mg –1 ·s –1 ·mL, respectively. V max , k cat , and k cat / K m decreased possibly because the substrate could not bind to the active sites of the immobilized pectinase because of the increased diffusion limitation.…”
Section: Resultsmentioning
confidence: 91%
“…Similar low K m values were earlier reported for the peroxidase activity of Cyt c using graphene oxide, silica nanoparticles, and polymer scaffold as supporting systems. 32 , 38 , 39 The K m value of the Cyt c –MoS 2 nanobiohybrid is significantly lower than that of the free Cyt c (123 mM). 41 This suggests that Cyt c has a higher substrate binding affinity when adsorbed on the MoS 2 nanosheets.…”
Section: Resultsmentioning
confidence: 94%
“…157 The conjugation of poly(acrylic acid) (PAA) carboxyl groups to the primary amines in Cyt c using carbodiimide coupling (Figure 7a) resulted in a 34-fold increase in peroxidase turnover number (k cat ). 158 Cyt c−PAA conjugates were produced with molecular weight ranging from 1.8k to 250k g mol −1 , and it was noticed that the k cat value for guaiacol oxidation was increased with increasing M W of PAA (Figure 7b). Enzyme activity studies at pH 6−8 indicated improved activity for Cyt c−PAA conjugates at neutral or slightly alkaline pH.…”
Section: Lysine and The N-terminusmentioning
confidence: 99%